An examination of decision-making during organizational crises: a case study of the 2017 Northern California Firestorm - Thomas, Cliff, author; Korte, Russell, advisor; Chermack, Thomas, committee member; Folkestad, James, committee member; Williams, Elizabeth, committee member (Colorado State University. Libraries, 2019)
Organizations experiencing crises are subject to harm that can involve injuries, fatalities, financial losses, reputational damage, losses of assets, and others. This study examined a phenomenon central to minimizing crisis-related harm: decision-making. More specifically, this study examined the ways in which decision elements interact to influence decision processes and behaviors during crises. The significance of this study stems from a steady increase in the frequency and intensity of organizational crises, and the claim that novel research and insights into the phenomenon can promote harm reduction. Research in this domain has been predominantly grounded in post-positivist perspectives, suggesting that new insights and understandings can be found through alternate perspectives. This inquiry adopted a constructivist and holistic view of crisis decision-making, recognizing that the construction of meaning, or "sensemaking", is an important aspect of decision-making. As such, this study sought to investigate how people make decisions during organizational crises, how and why some factors influence sensemaking and decision-making in the ways they do, how and why some decision factors are ascribed more significance than others, and the ways in which decision consequences influence ongoing decision-making. The conceptual framework guiding this study involved organizational crises, contextual decision factors, sensemaking frameworks, decision-making strategies, and decision consequences. The results of this study are intended to enlighten an area that some researchers and practitioners believe is growing in importance, and to provide insights that will foster improved practitioner capabilities. The study's findings suggest that in some contexts, organizational crisis decision-making can be appropriately described as a complex adaptive system. The findings also yielded insights related to several decision factors: past experiences, time influences, situational control, group member trust, and decision-maker self-perceptions. Among the various decision factors studied, decision-maker self-perceptions were found to be the most influential. Finally, implications for research, theory, and practice are presented.
Keywords: crisis management; organizational crisis; complex adaptive systems; sensemaking; decision-making